FAKTOR LINGKUNGAN KERJA DAN HUBUNGANNYA DENGAN KESEHATAN DAN KESELAMATAN KERJA - Ardiansyah; Widya Puspita Dewi; Putri Amelia Silvi; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2023)
The work environment is everything related to employee activities in the office. This starts from the company culture, physical environment, to supporting facilities, such as health insurance, parking, and so on. The factors that affect the work environment include: lighting or light, temperature or room temperature, humidity, air circulation, and noise levels.